2015
DOI: 10.1002/ceat.201400160
|View full text |Cite
|
Sign up to set email alerts
|

Selective Separation of Toluene/n‐Heptane by Supported Ionic Liquid Membranes with [Bmim][BF4]

Abstract: Room‐temperature ionic liquids serve as alternative solvents for volatile organic compounds in liquid‐liquid extraction and liquid membrane separation. 1‐Butyl‐3‐methylimidazolium tetrafluoroborate ([Bmim][BF4]) was applied for extraction and supported ionic liquid membranes (SILMs) to separate toluene and n‐heptane. A high separation factor of toluene was achieved due to the strong interaction between ionic liquid cations and toluene. The mass transfer performance of the SILM process was enhanced by higher op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
4
2
Order By: Relevance
“…The permselectivity goes through a maximum in the 50% ImC 11 TFSI system, which is dominated by diffusion coefficient differences (Table ), emphasizing the importance of understanding the effect of molecular details in separation membranes due to this unexpected maximum. The observed permselectivities are an order of magnitude larger than previous reports using ionic liquids for toluene–heptane separation. ,,,, However, the permselectivities found in the present work are overestimates, because real binary mixtures will competitively adsorb in the membrane. However, an important aspect of our work is that there is a maximum in the selectivity as a function of network density, which may outperform a linear PIL or a fully cross-linked network in a binary mixture test.…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…The permselectivity goes through a maximum in the 50% ImC 11 TFSI system, which is dominated by diffusion coefficient differences (Table ), emphasizing the importance of understanding the effect of molecular details in separation membranes due to this unexpected maximum. The observed permselectivities are an order of magnitude larger than previous reports using ionic liquids for toluene–heptane separation. ,,,, However, the permselectivities found in the present work are overestimates, because real binary mixtures will competitively adsorb in the membrane. However, an important aspect of our work is that there is a maximum in the selectivity as a function of network density, which may outperform a linear PIL or a fully cross-linked network in a binary mixture test.…”
Section: Resultscontrasting
confidence: 83%
“…The observed permselectivities are an order of magnitude larger than previous reports using ionic liquids for toluene−heptane separation. 14,15,26,36,38 However, the permselectivities found in the present work are overestimates, because real binary mixtures will competitively adsorb in the membrane. However, an important aspect of our work is that there is a maximum in the selectivity as a function of network density, which may outperform a linear PIL or a fully cross-linked network in a binary mixture test.…”
Section: ■ Results and Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…As observed in Table 6 , which summarizes the cases of SILMs applied to hydrocarbon separations, the investigated paraffins include aliphatic and cyclic hydrocarbons, while all the members of the BTEX family (Benzene, Toluene, Ethylbenzene and Xilenes) are included among the investigated aromatic compounds. Since the initial studies that demonstrated that these aromatic hydrocarbons were successfully transported through SILMs based on ILs such as [BMIM][PF 6 ], [HMIM][PF 6 ], [OMIM][PF 6 ] or [Et2MeMoEtN][NTf 2 ] [ 112 ], new research efforts were focused on the improvement of the selectivity of the SILMs and their stability [ 113 , 114 , 115 , 116 , 117 ]. Moreover, SILMs have demonstrated their validity for the removal of aromatics compounds from aqueous phases.…”
Section: Resultsmentioning
confidence: 99%
“…[54][55][56] It is also reported that when small amount of water was co-existed in an IL, the water molecule could be mainly distributed in a polar domain in the IL. [56] Because the imidazolium ring in the [C 4 mim][Tf 2 N] interacts with toluene though the C-H···π type of hydrogen bonding, [57,58] In the previous work, we also indicated that the light gas permeabilities of the DN ion gel membrane was dependent on the composition of inorganic and organic networks. [47] The CO 2 and N 2 permeabilities were increased with the increase of the inorganic network composition in the DN ion gel membrane with a constant IL content.…”
Section: Effect Of the Component In The Dn Ion Gel Membranementioning
confidence: 96%